PERAN DESENTRALISASI, AKUNTABILITAS, DAN SISTEM PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN KINERJA ORGANISASI PERANGKAT DAERAH - Ni Nyoman Padmawati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This study aims to examine the effect of decentralization, accountability and government management control systems on performance. The performance analyzed is the managerial performance of the leaders of local government organizations. This research was conducted at the regional organization of Buleleng Regency, Bali Province. By taking a sample of 30 organizational leaders. Which is then analyzed using multiple linear regression quantitative methods with the help of statistical tools. The sampling technique was done by random sampling. The results of the study indicate that the variables of decentralization, accountability and management control systems have a significant positive effect on the managerial performance of local government organizations. The higher the intensity of the implementation of fiscal decentralization, the higher the performance of Regional Apparatus Organizations in Buleleng Regency. This is because fiscal decentralization will determine a successful implementation of regional autonomy considering that fiscal decentralization will increase economic efficiency, improve accountability and increase fund mobilization. Accountability is one of the important elements in the realization of good governance relating to a person or organizational work unit to be responsible for the management and control of resources and the implementation of policies entrusted to him in the context of achieving the goals that have been set through the media of periodic accountability. The management control system variable on the performance of the Regional Apparatus Organization shows that the management control system has a positive and significant effect on the performance of the Regional Apparatus Organization.